A novel multiple impact model for predicting the residual stress state - Shan Cecilia Cao; Amy X.Y. Guo; Guilin Wu; Yudong Wang; Jian Lu; Xiaochun Zhang (Journal of Materials Research and Technology, 2023)
Developing ultrahigh-strength structural materials that are ductile, fracture resistant, and cost effective has been a long-standing desire for scientists and engineers. Surface nano-crystallization technology has recently been developed as one of the most effective methods to optimize surface structure, which can improve local and global mechanical behavior without compromising ductility. This technique involves the use of hundreds of small hard balls vibrated by high-power ultrasound so that they impact onto the surface of a material at high speed, also known as surface mechanical abrasion treatment (SMAT). Despite its success in enhancing the mechanical properties of steels and other structural materials, there is still lack of clear understanding of the relationships between desired surface structures/properties and controlling parameters in such surface treatment processes. Therefore, we calculated residual stress through computational modeling such as finite element analysis (FEA), and simulated the effect of all parameters during processing on residual compressive stress. Different multiple impact models are investigated to develop a more realistic model for the strengthening process.